Reporting an Experience: Improving the Feulgen Staining Technique for Better Visualizing of Nucleus - Noushin Jalayer naderi (Iranian Society of Pathology, 2018)
Among different staining methods used to demonstrate the nuclear abnormalities, Feulgen is one of the most reliable method. Feulgen staining is specific, sensitive method for evaluating the DNA damages.It has been shown that using non-DNA specific stains for monitoring the nuclear anomalies lead to false-positive or false-negative results. From self-experience, immersing the stained slides in hematoxylin for 3-5 minutes in final step after staining the slides with light green, provides a greater ground contrast and very better visualizing of nucleus. By this method, a clear distinction can be made between micronuclei and other structures suggestive of a micronucleus.